A metropolização e o mercado imobiliário: análise da produção do espaço a partir dos condomínios de chácaras da RMG - Lima, Leandro Oliveira de (2014)
The metropolis has been a special area of research in the media or even in Geography. The reasons themselves have been various and countless since the industrial revolution. In Brazil, a metropolis is a territory of dispute. Therefore, its natual way of concentrating goods, servicesand capital, along with the government funding programs in metropolitan areas such as PAC and My House My Life, cause many problems, among the ones most discussed by the press, such as health and education, besides spatial order as urban mobility, housing and sanitation. In these terms, the objective of this research is analyzing the production of the metropolitan area by the real estate market bias and the impacts of real estate brokers in converting rural land into condo farms. We believe that the real state actors from RMG, their acting and strategies are currently inducing the metropolitan sprawling. The pattern of fragmentation of urban land (whether for construction of apartment buildings for second homes, farms , exclusive condominiums or housing ) conducted by RMG follows the strategy of real estate developers with significant impact on reproduction and daily life of the metropoliscausing the pressure and appreciation of soil, causing even the gentrification of some areas of the metropolis goiana. In these terms, our thesis was that the local stock actors in association with the concentration of surplus income from Goiania altered the metropolis to trigger rural stocks from RMG as a condition for the reversal of capital. Even if not fully dense, the condos farms operate as "store of value" and serve the interests of a small portion of goianienses. This fact, expressed as spatial response of the real estate actors encouraged us to observe the character of concentrating income from space. The existence of a market for integrated land and the accumulation of economic power in the RMG made the metropolitan spatial production an important issue for Geography in Goiânia. From a methodological standpoint, our data collecting involved gathering primary and secondary information, document analysis and mapping. These steps enabled the correlation processes sociogeographic about RMG. The metropolis is / was the scale of investigation and intervention, both for research and for the actors of the metropolitan space. The contribution of this research lies in the discussion of vertical condominiums farms as a new pattern of use, ownership and housing in metropolitan environments, as well as intervention strategies of the actors of the real estate market in the process of making space.